Comprehensive molecular cytogenetic analysis of Barbary macaque (Macaca sylvanus) - X. Fan; W. Sangpakdee; A. Tanomtong; Chaveerach, A.; K. Pinthong; S. Pornnarong; W. Supiwong; V. Trifonov; G. Hovhannisyan; K. Loth; C. Hensel; T. Liehr; et al. (ՀՀ ԳԱԱ հրատ.)
Origin of human and ape chromosomes has been studied by comparative chromosome banding analysis and by fluorescence in situ hybridization (FISH). As it is not always possible to determine exact breakpoints and distribution or orientation of specific DNA stretches by these approaches FISH-banding was applied in the present study to reanalyze the chromosomes of Barbary macaque (Macaca sylvanus). Interestingly, the results agree with those of previous studies in other macaques, supporting the idea that the genetic differences leading to the observed large morphological differences within the Ceropithecoidae still have to be discovered.
Keywords: Biology; Histology